Shikonin Ameliorates LPS-Induced Cardiac Dysfunction by SIRT1-Dependent Inhibition of NLRP3 Inflammasome - Guo, Tao; Jiang, Zhong-Biao; Tong, Zhong-Yi; Zhou, Yang; Chai, Xiang-Ping; Xiao, Xian-Zhong (Frontiers in Physiology, 2020)
Shikonin is an anti-inflammatory agent extracted from natural herbs. The aim of this study is to explain the treatment effects and mechanism of Shikonin on LPS-induced myocardial inflammation and dysfunction. A mouse model of LPS-induced cardiac dysfunction was established by intraperitoneal injection of LPS. Firstly, we evaluated the effect of Shikonin on the anti-inflammation of heart tissue in sepsis mice. Secondly, the expression of SIRT1, NLRP3 and Caspase1 were examined by WB in vivo and vitro, the release of inflammatory cytokines was measured by ELISA in serum and supernatant of cell culture. Finally, the mechanism of Shikonin on the anti-inflammation induced by LPS was studied in vitro. We found that SHI treatment remarkably ameliorated inflammatory factors release and macrophage infiltration in heart tissue, and elevated the survival rate in LPS-treated mice.SHI reversed the reduction of SIRT1 in LPS-treated heart tissue and H9C2 cardiomyocytes. In addition, SIRT1 inhibitor was found to block SHI-mediated cardioprotective effects, while SIRT1 activator acted to enhance the anti-inflammatory effect of Shikonin in vitro. These results showed that Shikonin has anti-inflammatory effects induced by LPS via SIRT1-dependent pathways. Moreover, our study found the expressions of NLRP3 and caspase1 were increased in LPS-treated mice and H9C2 cardiomyocytes. However, SHI inhibited the expression of NLRP3 and caspase1 in vivo and in vitro.Our study confirmed that SHI could ameliorate LPS-induced cardiac dysfunction and inhibit NLRP3 inflammasomes activation by SIRT1-dependent pathways.Shikonin ameliorate LPS-induced cardiac dysfunction